Meeting the Challenges of COVID-19: Evaluation of Nurse-Led Changes to Telephonic Assessment. (July 2022) - Squeri, Barbara; Gayton, Matthew; Huang, Jennifer; Chavez, Silvia; Souffront, Kimberly
Abstract : The early months of the COVID-19 pandemic caused suspension of physician home visits at our NYC home-based primary care practice as well as disruptions in community-based services homebound patients rely on. This produced gaps in care for a vulnerable patient population that is considered underserved and medically and socially complex. Telephone triage nurses at Mount Sinai Visiting Doctors Program responded to these gaps in care with targeted enhancements to telephonic patient assessment: creating an encrypted email address to receive photographs, the use of two Epic dot phrases to screen and educate regarding COVID-19, assessment of patients' ability to complete a video visit, the reassessment of goals of care, and the assessment of changes in home care services. We surveyed 15 attending physicians in our practice to evaluate primary care providers' opinions regarding changes in nurse telephone triage and how helpful they were in managing patients at home during the early pandemic. We found enhancements to nurse telephone triage were viewed by physicians as beneficial, valuable, and improved patient care. Physicians found changes improved timeliness of care, could improve self-management, helped avoid transfer to emergency department, and helped manage patient care at home. As the pandemic continues and telehealth becomes more widely used, nurse telephone triage may be adaptable to help care for a variety of patient populations during future public health emergencies.